FEATURES OF STRATEGIC MANAGEMENT ORGANIZATIONS CONSTRUCTION SECTOR OF THE ECONOMY - I. Kogotkova; A. Sal’Nik (Вестник университета)
In the investigation as a subject of investigation was defined development strategy sector «construction». The purpose of the investigation is to examine the development strategies of construction companies. Also, in the article was formulated mission of the construction sector, as well as on its basis were identified several key areas of the studied branch of activity. During the investigation were examined the main business development strategy in the construction sector.